"Just like us": migrancy, photography, and visual incorporation. (4th May 2021) - Dean, Alison V.
Abstract : This article considers how the relatively new genre of migrant photography, "the migrant selfie, " fits into the larger visual history of migrancy. From early UNHCR photography to contemporary representations of migration in the news and visual art, this paper traces the visual image of the migrant over time. It then draws on this history to contextualize selfies featured in Tomas van Houtryve's (2016–2017) video installation, Traces of Exile .